A new genus of fossil frog (Anura) from lower Cretaceous deposits in South America - Moura, Pedro Henrique A.g. [UNESP]; Costa, Fabiana R.; Anelli, Luiz E.; Nunes, Ivan [UNESP] (Academia Brasileira de Ciências, 2021)
The frog clade Neobatrachia or “advanced frogs” represents more than 95% of the diversity within Anura. The neobatrachian fossil record is incomplete due to the small size and fragile nature of their bones but provides some clues on the time and rate of the current diversification of modern-day amphibians. The Crato Formation (Aptian) of northeastern Brazil is known for the presence of, at least, five species of neobatrachian fossils. Herein, we describe a well-preserved fossil that represents a new neobatrachian taxon from the Crato Formation (Cretaceous) in the Araripe Basin, northeastern Brazil, and perform phylogenetic analysis to assess its higher-level relationships. The new specimen is an almost complete and articulated skeleton with soft tissue preservation. Phylogenetic analysis recovered the specimen nested in the clade Hyloidea and our results highlight the remarkable value of the Crato Formation as a Laggerstätte.
Keywords: Amphibia; fossil anuran; Cretaceous; Primaevorana cratensis